Technology’s influence on student engagement in online learning - Quynh, Ngo Hai; Hoai, Nguyen Thanh (Intelektual Pustaka Media Utama, 2026)
Online learning has become an indispensable learning method in an environment of unpredictable changes. This study was conducted with the aim of assessing the factors affecting students’ satisfaction and engagement in learning under the influence of technology. A survey of 368 university students experienced in online learning in Da Nang, Vietnam, yielded 339 valid responses. Data analysis employed Microsoft Excel, SPSS, and AMOS, with hypotheses tested via structural equation modeling (SEM). Service quality, student expectation and perceived enjoyment positively impact student satisfaction with perceived enjoyment having the strongest effect. Increased satisfaction significantly enhances student engagement. Ease of use, however, does not significantly affect satisfaction. The findings reflect cultural and contextual differences, consistent with global studies. The study emphasizes creating enjoyable, high-quality, and expectation-aligned learning experiences to boost satisfaction and engagement. Educational administrators should prioritize a culture of lifelong learning, the service-oriented spirit of lecturers, expectation management, and engaging learning environments, personal enjoyment and social factors such as knowledge sharing and collaboration. This research highlights the unique dynamics of online learning, emphasizing the influence of cultural factors on student satisfaction and engagement.